AMELIORATIVE EFFECTS OF Withania somnifera ROOT POWDER ON GROWTH PERFORMANCE IN LEAD TREATED CHICKENS (Indian Journal of Animal Production and Management, 2016)
The present study was carried out to evaluate the toxic effect of lead and protective efficacy of Withania  somnifera root powder on the growth and performance of chickens for a period of 60 days. The general  performance of birds was evaluated on the basis of clinical signs, average weekly body weight, feed  consumption, body weight gain and feed conversion ratio (FCR). In control group (group I), birds were  active and healthy and did not show any untoward clinical sign. While in 250 ppm (group II) and 400 ppm  (group III) lead treated birds showed signs like dullness, depression, weakness, letharginess with loss of  appetite. Loose droppings were seen in group III. Clinical signs were less severe with less number of birds  affected in 250 ppm lead+WSRP (group IV) and 400 ppm+WSRP (group V) birds as compared to groups II  and III. No mortality was seen in any of the group. A significant dose and time dependent decrease in body  weight, feed consumption, body weight gain and significant increase in FCR were observed in groups II and  III as compared to group I. However, in groups IV and V, a significant lesser decrease in body weight, feed  consumption, body weight gain and significantly less increase in FCR observed as compared to groups  II and III observed, respectively. The present investigation indicated the adverse effects of lead acetate  on performance of broilers at 250 and 400 ppm and Withania somnifera root powder offering protection  against lead toxicity in chickens.
Keywords: Chickens; Growth performance; Lead; Withania somnifera